2017
DOI: 10.1007/s11948-017-9872-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Implications of User Perceptions of Wearable Devices

Abstract: Health Wearable Devices enhance the quality of life, promote positive lifestyle changes and save time and money in medical appointments. However, Wearable Devices store large amounts of personal information that is accessed by third parties without user consent. This creates ethical issues regarding privacy, security and informed consent. This paper aims to demonstrate users' ethical perceptions of the use of Wearable Devices in the health sector. The impact of ethics is determined by an online survey which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…Mobile app data security continues to be an area of concern for the industry. Many authors discuss the vulnerabilities of data when being stored or during transmission to third parties [28,74,75]. There is still some debate in the literature about the security risks and benefits of the cloud; while some authors fear that cloud infrastructure is more susceptible to privacy and security attacks [76], others postulate that cloud service providers may address data privacy and security more effectively due to economies of scale and scope, which enable them to maintain more sophisticated defenses against cyber-attacks [77].…”
Section: Themes Data Transmission and Storagementioning
confidence: 99%
See 4 more Smart Citations
“…Mobile app data security continues to be an area of concern for the industry. Many authors discuss the vulnerabilities of data when being stored or during transmission to third parties [28,74,75]. There is still some debate in the literature about the security risks and benefits of the cloud; while some authors fear that cloud infrastructure is more susceptible to privacy and security attacks [76], others postulate that cloud service providers may address data privacy and security more effectively due to economies of scale and scope, which enable them to maintain more sophisticated defenses against cyber-attacks [77].…”
Section: Themes Data Transmission and Storagementioning
confidence: 99%
“…That same study showed that 40% of the apps failed to protect the integrity of the data they displayed [91]. Other authors also expressed concerns that data integrity could be compromised as a result of attacks during transmission over public networks or simply due to immature sensor-based technology [74,75,78,80,92]. Another oft-cited concern regarding data collected outside of the clinical setting regards its authenticity, accuracy, and provenance [92,93].…”
Section: Themes Data Transmission and Storagementioning
confidence: 99%
See 3 more Smart Citations